Evaluación de la eficiencia de fungicidas sobre el control de enfermedades en rendimiento y calidad del grano en híbridos de maíz (Zea mays L.), en la zona del Empalme. - Pazmiño López, Euclides Liviston (2017)
The present work was carried out in the property of Mr. José Sánchez, located in the Pedro Vélez - Vía a Pichincha Precinct Guayas Province El Empalme. The geographical coordinates are Latitude: S 00º49' and Longitude: O 79º22 ', to an altitude of 131 msnm. The general objective of the present study was to: Determine the effectiveness of fungicide application on the control of diseases in maize (Zea mays L.) hybrids, and the specific objectives were: 1: To evaluate the effectiveness of fungicides on disease control in maize commercial hybrids, 2: Establish the dose and frequency of application of fungicides on disease control in maize cultivation, 3: Carry out economic analysis of yield Corn based on the cost of the treatments under study. The hybrids studied were 3 commercial Tropi 101, DK 7088 and Pac 105, which corresponded to the treatments under study in the area of El Empalme. For this area, the experimental design Bloques Completos A Azar (BCA) with factorial arrangement of 3 x 6 +1 in three replicates was used. The Tukey test was applied to 95% to establish the statistical differences between the means of the hybrids to determine the statistical differences of this zone. Plant height, grain quality, disease severity and incidence, ear length, cob diameter, number of rows per ear, ear insertion height, grain / tusa ratio, number of plants at harvest , Yield and the economic analysis was finally carried out. Based on the interpretation and analysis of the results it was concluded that hybrids did not reach statistical significance in plant height, disease incidence at 39, 50 and 80 days after application of fungicides, indicating that hybrids did not Were influenced by the application, ie showed a similar behavior in terms of susceptibility or resistance to diseases. The largest diameter of ear was reached with the hybrid Tropi 101 with 2.9 cm, more than the hybrids Pac 105 and DK 7088. Key Words: Maize, Fungicides and Yield.